PENERAPAN TEKNOLOGI RAPID DALAM SISTEM MANUFAKTUR PRODUK ELEKTRONIKAKASUS RANGKAIAN UNIVERSAL PID CONTROLLER - Mahmud; RumintoSubekti; Suharyadi Pancono (Politeknik Aceh, 2016)
The production processesof electronics parts faced with many constraints such as: shape, size, type, material, length, width, and height of enclosure and customized electronics module. Therefore, rapid production method is applied as the solution to hasten it.Rapid production method applied in this research consists of some variations of process, among of them; PDS(parametric drawing system), laser cutting machine, CNC PCB Router machine. PDS is used for processing enclosure design in which user interface PDS is assembled with VBA (visual Basic for Application) in CorelDraw X6.The advantage of PDS is the speed of drawing process is shorter than non-parametric. Laser cutting machine is used for processing enclosure production. CNC PCB router is used for processing of electronics circuits PCB production. The implementation results from laser cutting machine in acrylic materials with width 8 mm, are obtained with the speed 2 mm/s to 8 mm/s, and power 60 % to 90 %, while the implementation result from CNC PCB router for process of marking, routing, drilling, contouring in PCB FR4 materials is 1.55 mm in ± 11 minutes.